Anatomy and function of the fornix in the context of its potential as a therapeutic target. Issue 5 (4th March 2020) - Senova, Suhan; Fomenko, Anton; Gondard, Elise; Lozano, Andres M
Abstract : The fornix is a white matter bundle located in the mesial aspect of the cerebral hemispheres, which connects various nodes of a limbic circuitry and is believed to play a key role in cognition and episodic memory recall. As the most prevalent cause of dementia, Alzheimer's disease (AD) dramatically impairs the quality of life of patients and imposes a significant societal burden on the healthcare system. As an established treatment for movement disorders, deep brain stimulation (DBS) is currently being investigated in preclinical and clinical studies for treatment of memory impairment in AD by modulating fornix activity. Optimal target and stimulation parameters to potentially rescue memory deficits have yet to be determined. The aim of this review is to consolidate the structural and functional aspects of the fornix in the context of neuromodulation for memory deficits. We first present an anatomical and functional overview of the fibres and structures interconnected by the fornix. Recent evidence from preclinical models suggests that the fornix is subdivided into two distinct functional axes: a septohippocampal pathway and a subiculothalamic pathway. Each pathway's target and origin structures are presented, followed by a discussion of their oscillatory dynamics and functional connectivity. Overall, neuromodulation of each pathway of the fornix is discussed in the context of evidence-based forniceal DBS strategies. It is not yet known whether driving fornix activity can enhance cognition—optimal target and stimulation parameters to rescue memory deficits have yet to be determined.